2006
DOI: 10.4012/dmj.25.455
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Morphological and Thermal Effects of 10.6-.MU.m CO2 Laser on the Inhibition of Enamel Demineralization

Abstract: Studies have shown that enamel can be modified by pulsed CO 2 laser to form a more acid-resistant substrate. This study evaluated the effects of a 10.6-μm CO 2 laser on enamel surface morphology and chemical composition as well as monitored intrapulpal temperature changes during irradiation. Human teeth were irradiated with fluences of 1.5 -11.5 J/cm 2 , and pulpal thermal as well as chemical and morphological modifications on enamel were assessed. The teeth were submitted to a pHcycling model, and the mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 40 publications
7
53
0
18
Order By: Relevance
“…8,9,10 Furthermore, some authors have concluded that laser irradiation associated with fluoride agents 11,12 could increase the fluoride uptake into the enamel, making the enamel more acid resistant. 11,13 However, until now, there have been only a few studies 12,14,15,16 evaluating the use of CO 2 lasers to prevent dental erosion, and these studies have been inconclusive.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…8,9,10 Furthermore, some authors have concluded that laser irradiation associated with fluoride agents 11,12 could increase the fluoride uptake into the enamel, making the enamel more acid resistant. 11,13 However, until now, there have been only a few studies 12,14,15,16 evaluating the use of CO 2 lasers to prevent dental erosion, and these studies have been inconclusive.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…10 Since the intervention of ruby crystal laser by Maiman in 1960, different lasers have been assessed in dentistry fields. 15 Different types of lasers such as Er: YAG, Nd: YAG and CO 2 with various adjusting parameters have been administrated for caries prevention. CO 2 lasers are useful without hazardous side effects and they keep surface temperature at safe levels.…”
Section: Effect Of Co2 Laser and Fluoride Varnish Application On Micrmentioning
confidence: 99%
“…The main chemical changes in enamel due to photothermal effects are that the prevailing CO 3 component in the phosphate position decreases and the acid phosphate ions condense to form pyrophosphate ions. At higher temperatures occurs a thermal re-crystallization and crystal size growth and the pyrophosphate reacts with apatite to form PO 4 . The hypothesis is that these effects make enamel less soluble to acids (4).…”
Section: Introductionmentioning
confidence: 99%
“…At higher temperatures occurs a thermal re-crystallization and crystal size growth and the pyrophosphate reacts with apatite to form PO 4 . The hypothesis is that these effects make enamel less soluble to acids (4).…”
Section: Introductionmentioning
confidence: 99%